BRAZILIAN SECURITY POLICY IN THE AMAZON BORDER AND SECURITIZATION OF THE COLOMBIAN CONFLICT (2001-2011) - Rego Monteiro, Licio (Hemisferio - Revista del Colegio Interamericano de Defensa, 2016)
The cross-border effects of the Colombian conflict occurred unevenly in each neighboring country. The merging of the Colombian conflict with the global war on terrorism in 2002 was a turning point for the responses of neighboring countries. For Brazilian border policies, the main impact of this turning point was to reinforce the trend toward militarizing the institutional presence at the Brazil-Colombia border and in the entire Amazon region. The Brazilian government's responses did not occur only in a traditional way of closing the borders, but with new modalities of border control, with a focus on the cross-border illegal flows. The mapping produced by this research demonstrates that the current profile of Brazilian policies for border security was strongly influenced by the responses to challenges brought about by the Colombian conflict. It can be showed by the mapping. The result of this process represented a shift in the policies related to the continental border of Brazil. Considering security and development as two main drivers of Brazilian government approach at the border, we note that a focus on security issues, at the expense of cross-border regional development, has prevailed in recent years. Another possibility is to consider regional cooperation on security as a means to achieve better results in regional development and integration.